Preclinical efficacy and safety analysis of gamma-irradiated inactivated SARS-CoV-2 vaccine candidates - Gozde Sir Karakus; Cihan Tastan; Derya Dilek Kancagi; Bulut Yurtsever; Gamze Tumentemur; Sevda Demir; Raife Dilek Turan; Selen Abanuz; Didem Cakirsoy; Utku Seyis; Samed Ozer; Omer Elibol; et al. (Scientific Reports, 2021)
Abstract COVID-19 outbreak caused by SARS-CoV-2 created an unprecedented health crisis since there is no vaccine for this novel virus. Therefore, SARS-CoV-2 vaccines have become crucial for reducing morbidity and mortality. In this study, in vitro and in vivo safety and efficacy analyzes of lyophilized vaccine candidates inactivated by gamma-irradiation were performed. The candidate vaccines in this study were OZG-3861 version 1 (V1), an inactivated SARS-CoV-2 virus vaccine, and SK-01 version 1 (V1), a GM-CSF adjuvant added vaccine. The candidate vaccines were applied intradermally to BALB/c mice to assess toxicity and immunogenicity. Preliminary results in vaccinated mice are reported in this study. Especially, the vaccine models containing GM-CSF caused significant antibody production with neutralization capacity in absence of the antibody-dependent enhancement feature, when considered in terms of T and B cell responses. Another important finding was that the presence of adjuvant was more important in T cell in comparison with B cell response. Vaccinated mice showed T cell response upon restimulation with whole inactivated SARS-CoV-2 or peptide pool. This study shows that the vaccines are effective and leads us to start the challenge test to investigate the gamma-irradiated inactivated vaccine candidates for infective SARS-CoV-2 virus in humanized ACE2 + mice.